2012
DOI: 10.1002/jor.22101
|View full text |Cite
|
Sign up to set email alerts
|

The natural compound Alizarin as an osteotropic drug for the treatment of bone tumors

Abstract: Despite significant clinical improvements, conventional therapies for bone cancer treatment are limited by significant systemic toxicity and lack of specific targeting. In this study, we considered Alizarin, a natural hydroxyanthraquinone derived from madder root with high affinity to calcium and remarkable osteotropic features, as a novel approach for bone cancer treatment. Due to its antitumor properties, as demostrated in colon cancer cells, and to its tropism to bone, Alizarin may be an ideal drug to reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 38 publications
0
32
2
Order By: Relevance
“…Although maximal dose escalation of conventional chemotherapy has been utilized, there is still no significant gain in clinical outcome. The use of conventional antitumor drugs, such as doxorubicin and methotrexate, is usually limited due to their systemic toxicity and lack of specificity [19]. Furthermore, no effective standard second-line chemotherapeutic agent has been identified in local or distant relapsed osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Although maximal dose escalation of conventional chemotherapy has been utilized, there is still no significant gain in clinical outcome. The use of conventional antitumor drugs, such as doxorubicin and methotrexate, is usually limited due to their systemic toxicity and lack of specificity [19]. Furthermore, no effective standard second-line chemotherapeutic agent has been identified in local or distant relapsed osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Alizarin 7 was found to have a better antioxidant activity when compared with green tea polyphenol and vitamin E 35 . In additional, alizarin (7) also showed good cytotoxicity against osteosarcoma and breast carcinoma cells 36 . It also exhibits immunosuppressive activity 37 .…”
Section: Biotransformation Of Hydroxyanthraquinonesmentioning
confidence: 99%
“…Alizarin (ALZ) is a red, natural, non‐toxic hydroxyanthraquinone drug derived from the madder root that has been mainly used for dying fabrics, or as a staining reagent to stain murine cartilage and bone . Caterina Fotia and co‐workers reported that ALZ can be used in the treatment of bone marrow tumors . In the present study, for the first time, we report the use of ALZ as a spectroscopic probe for the interaction of the neutral drug, ATN, with DNA.…”
Section: Introductionmentioning
confidence: 55%
“…[34] Caterina Fotia and co-workers reported that ALZ can be used in the treatment of bone marrow tumors. [35] In the present study, for the first time, we report the use of ALZ as a spectroscopic probe for the interaction of the neutral drug, ATN, with DNA.…”
Section: Introductionmentioning
confidence: 81%